The Relationship of Early Mobilization and Nutrition Factors with the Wound Healing Process of Post Sectio Caesarea at Putri Hijau Hospital, West Medan District, Medan City in 2021 - Sumiatik (Science Midwifery, 2022)
It is estimated that 60% of maternal deaths due to pregnancy occur after delivery and 50% of postpartum mass deaths occur within the first 24 hours. Nationally, the incidence of infection during the puerperium reached 2.7% and 0.7% developed towards acute infection. The cause of the high rate of infection is the decrease in the immune system of pregnant women who are susceptible to infection. Infection can occur because mothers give birth in health workers who use non-sterile tools. The infection that usually occurs in postpartum mothers is puerperal sepsis (Hastuti, 2012). This type of research is quantitative with a survey research design using a cross sectional approach. The population is all postpartum mothers who gave birth by caesarean section at Putri Hijau Hospital totaling 35 people and a sample of 30 people, using acideental sampling technique. The data collected in this study is primary data, namely data obtained directly from respondents by using a questionnaire. Data analysis using Chi Square statistical test The results of the statistical analysis of early mobilization, the majority did not mobilize as many as 17 (56.7%) respondents with slow post Sc wound healing as many as 15 (50%) with 0.001 <0.05. The majority of nutrition is normal nutrition as many as 12 (40%) respondents with fast post sc wound healing as many as 12 (40%). Based on statistical results using Chi-Square shows a p value of 0.000 which is smaller than the level of error (0.000 <0.05). So Ho was rejected and Ha was accepted, meaning that there was a relationship between early mobilization and nutrition with the Post Sectio Caesarea Wound Healing Process at Putri Hijau Hospital in 2021. The wound healing process of each individual varies, but early mobilization must still be carried out after SC surgery considering the many benefits obtained. Without ignoring other supporting factors such as nutrition, oxygenation, drug use and so on